Efficient algorithms for computing the largest eigenvalue of a nonnegative tensor - Zhou, Guanglu; Qi, Liqun; Wu, Soon-Yi (Springer, 2013)
Consider the problem of computing the largest eigenvalue for nonnegative tensors. In this paper, we establish the Q-linear convergence of a power type algorithm for this problem under a weak irreducibility condition. Moreover, we present a convergent algorithm for calculating the largest eigenvalue for any nonnegative tensors.